Dimensions of Religiousness and Cancer Screening Behaviors Among Church-Going Latinas - Allen, Jennifer D. (Journal of religion and health, 2014)
Churches are a promising setting through which to reach Latinas with cancer control efforts. A better understanding of the dimensions of religiousness that impact health behaviors could inform efforts to tailor cancer control programs for this setting. The purpose of this study was to explore relationships between dimensions of religiousness with adherence to cancer screening recommendations among church-going Latinas. Female Spanish-speaking members, aged 18 and older from a Baptist church in Boston, Massachusetts (N = 78), were interviewed about cancer screening behaviors and dimensions of religiousness. We examined adherence to individual cancer screening tests (mammography, Pap test, and colonoscopy), as well as adherence to all screening tests for which participants were age-eligible. Dimensions of religiousness assessed included church participation, religious support, active and passive spiritual health locus of control, and positive and negative religious coping. Results showed that roughly half (46 %) of the sample had not received all of the cancer screening tests for which they were age-eligible. In multivariate analyses, positive religious coping was significantly associated with adherence to all age-appropriate screening (OR = 5.30, p < .01). Additional research is warranted to replicate these results in larger, more representative samples and to examine the extent to which enhancement of religious coping could increase the impact of cancer control interventions for Latinas.